Pelatihan Pembuatan Karya Tangan Minimalis Bernilai Ekonomis Di Desa Jarak Kabupaten Kediri - Nabila Andriani; Afif Nur Rahmadi; Nonni Yap; Andy Chandra Pramana (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
someone can turn waste into a handicraft that can generate profits and moreover can be sold. Cardboard waste is one of the wastes that can be reprocessed into a useful handicraft. By empowering existing human resources in Jarak Village, Plosoklaten District, Kediri Regency, this Community Service activity is carried out by providing entrepreneurial insight, providing training to make handicrafts from cardboard waste. As a result of this activity, the community in the Jarak Village, Ploso Klaten District, Kediri Regency, got additional entrepreneurial insights which included how to obtain raw materials, production techniques, and product marketing.